Recovery of Ammonium Metavanadate from Spent Catalyst - Aliwarga, Lienda; Ramadianti Musadi, Maya (Jurnal Rekayasa Kimia & Lingkungan, 2020)
Utilization of spent catalysts serves to meet the needs of vanadium and to overcome the environmental problem since vanadium is categorized as a hazardous, toxic material. Vanadium from the spent catalysts can be recovered in the form of V2O5 or NH4VO3. However, vanadate compounds (NH4VO3) are considered to be more valuable due to their higher price and easier production process, compared with V2O5. This study aims to find adequate operating conditions to obtain high yields and high purity of NH4VO3 crystals. The results showed that the presence of iron compounds in the extract made the crystals contaminated by brownish colour, so it decreased its purity. Therefore, iron compounds need to be separated first with precipitation. Crystals of NH4VO3 with yield of 60% on spent catalysts and purity of 75% were obtained by extraction using solvent Na2CO3 1.887 M for 60 minutes at room temperature with weight ratio of V2O5 in spent catalyst toward solvent volume (Rvp), 0.006 gram V2O5/mL Na2CO3. It was then continued by precipitation of iron compounds at pH of 12 for 2 hours and crystallization of NH4VO3 using NH4Cl 11.215 M for 4 - 5 hours at 60oC.